IMPLEMENTATION OF RECOVERY AND DEVELOPMENT OF SOCIAL FUNCTIONS OF ELDERLY INTEGRATED CITIZENS IN CLASS IIB COMMUNITY INSTITUTIONS GUNUNGSITOLI - Zega, Lucky Tabarman; Simanjuntak, Meitisa Vanya (Universitas Nusa Cendana, 2025)
Correctional institutions are institutions or places that carry out the function of coaching inmates and children of correctional inmates. One of the coaching sessions in the prison is carried out for inmates of vulnerable groups, such as the elderly. One of the actions for the elderly inmates is the recovery and development of social functions. The purpose of this study is to analyze the implementation of the recovery and development of social functions, as well as the obstacles that occur in the implementation for elderly inmates in the Gunungsitoli Class IIB prison. The data sources of this study are taken from primary and secondary data. The data collection technique in this study uses interviews, observation, and documentation methods. The result of this research is the implementation of the restoration and development of social functions in the Gunungsitoli Class IIB Prison, namely spiritual worship, religious lectures, and gymnastics activities. The obstacles in the implementation of this are the physical, spiritual, and psychological limitations of elderly inmates and their families, who do not play an active role. Keywords: Implementation; Recovery; Inmates; Elderly